Morphological and Molecular Characterization of Filenchus multistriatus n. sp. (Tylenchomorpha: Tylenchidae) and Data on a Known Species of the Genus from Bushehr Province, Southern Iran - Monemi Somayeh; Atighi Mohammad Reza; Abolafia Joaquín; Castillo Pablo; Pedram Majid (Journal of Nematology, 2023)
During a nematological survey in southern Iran, a population belonging to the family Tylenchidae was recovered from a tomato field in Bushehr province. The recovered population belongs to the genus Filenchus, was described and illustrated herein as F. multistriatus n. sp. It is mainly characterized by having a wide and low annulated lip region continuous with adjacent body; amphidial openings confined to the labial plate; four lines in lateral fields forming three bands, with the two outer bands broken by transverse, and the inner one broken by both transverse and longitudinal lines; and median bulb oval with visible valve and elongate-conoid tail uniformly and gradually narrowing toward the distal region, ending in a widely rounded tip. Its morphological and morphometric differences with three closely similar species were discussed. The phylogenetic relationships of the new species with other relevant genera and species were reconstructed using partial sequences of small, and large subunit ribosomal DNA (SSU and LSU rDNA) sequences. Morphometric and morphological data were also provided for an Iranian population of F. sandneri recovered from Bushehr province. Both populations were characterised using SEM data.